Assessment of daily dose accumulation for robustly optimized intensity modulated proton therapy treatment of prostate cancer. (January 2021) - Xu, Yihang; Diwanji, Tejan; Brovold, Nellie; Butkus, Michael; Padgett, Kyle R.; Schmidt, Ryder M.; King, Adam; Dal Pra, Alan; Abramowitz, Matt; Pollack, Alan; Dogan, Nesrin
Highlights: Daily CBCTs were used for creation of the synthetic CTs for dose accumulation. RO-IMPT±3mm/±3% plans are superior to RO-IMPT±5mm/±3% for prostate IMPT plans. Prostate IMPT ± 5 mm/±3% robust evaluation can predict the daily DVH fluctuation range. Weekly accumulated dose can estimate the overall dose delivered to prostate patients. Abstract: Purpose: To implement a daily CBCT based dose accumulation technique in order to assess ideal robust optimization (RO) parameters for IMPT treatment of prostate cancer. Methods: Ten prostate cancer patients previously treated with VMAT and having daily CBCT were included. First, RO-IMPT plans were created with ± 3 mm and ± 5 mm patient setup and ± 3% proton range uncertainties, respectively. Second, the planning CT (pCT) was deformably registered to the CBCT to create a synthetic CT (sCT). Both daily and weekly sampling strategies were employed to determine optimal dose accumulation frequency. Doses were recalculated on sCTs for both ± 3 mm/±3% and ± 5 mm/±3% uncertainties and were accumulated back to the pCT. Accumulated doses generated from ± 3 mm/±3% and ± 5 mm/±3% RO-IMPT plans were evaluated using the clinical dose volume constraints for CTV, bladder, and rectum. Results: Daily accumulated dose based on both ± 3mm/±3% and ±5 mm/±3% uncertainties for RO-IMPT plans resulted in satisfactory CTV coverage (RO-IMPT3mm/3% CTVV95  = 99.01 ± 0.87% vs. RO-IMPT5mm/3% CTVV95  = 99.81 ± 0.2%, P = 0.002). However, the accumulated dose based on ± 3 mm/3% RO-IMPT plans consistently provided greater OAR sparing than ±5 mm/±3% RO-IMPT plans (RO-IMPT3mm/3% rectumV65Gy  = 2.93 ± 2.39% vs. RO-IMPT5mm/3% rectumV65Gy  = 4.38 ± 3%, P < 0.01; RO-IMPT3mm/3% bladderV65Gy  = 5.2 ± 7.12% vs. RO-IMPT5mm/3% bladderV65Gy  = 7.12 ± 9.59%, P < 0.01). The gamma analysis showed high dosimetric agreement between weekly and daily accumulated dose distributions. Conclusions: This study demonstrated that for RO-IMPT optimization, ±3mm/±3% uncertainty is sufficient to create plans that meet desired CTV coverage while achieving superior sparing to OARs when compared with ± 5 mm/±3% uncertainty. Furthermore, weekly dose accumulation can accurately estimate the overall dose delivered to prostate cancer patients.